Development of a continuous evaporation system for an API solution stream prior to crystallization. Issue 11 (26th August 2021) - Roche, Phillip; Jones, Roderick C.; Glennon, Brian; Donnellan, Philip
Abstract: A bubble column was investigated as a method to achieve a desired and controllable rate of evaporation of a pharmaceutical solution. Applying a thermodynamic model to predict the rate of evaporation, all predicted values were observed to have accuracies within the bounds of instrumentation errors (<5% absolute). The developed model accounted for the measured effect of reduced vapor pressure, caused by the dissolved solids as a function of their concentration. A general method to obtain accurate measurement of this effect is introduced and applied, improving the accuracy of model predictions. Consistent and repeatable evaporation rates ranging from 0.7 to 6.9 g/min were achieved experimentally, and errors between predicted rates and observed ranged from 0.219% to 4.19% absolute. This demonstrates a controllable and flexible method for the evaporation of process streams which can be compared to harsher conventional methods such as boiling. The column was configured in a continuous mode and coupled to a downstream crystallizer (MSMPR). Using the column as a controllable concentrator, the concentration of a dilute feed stream of paracetamol in methanol was increased in a single equilibrium stage. The column demonstrated the ability to concentrate the solution in flow by 179%, delivering a flow of 2 ml/min of concentrated liquor to the MSMPR. The MSMPR achieved steady‐state of control, measured by offline dissolved concentration analysis and particle count by FBRM in situ, highlighting the applicablity of the column to perform reliably in a continuous tandem.